Half a Century of Temperate Non-Forest Vegetation Changes No Net Loss in Species Richness, but Considerable Shifts in Taxonomic and Functional Composition - Klinkovská, Klára (Global change biology, 2025)
© 2025 The Author(s). Global Change Biology published by John Wiley & Sons Ltd.